The spillover effect of US monetary policy on the international financial market: Evidence from network analysis - Ying Hou; Wei Li; Dexiang Wu; Ying Zang; Long Quach (Journal of Management Science and Engineering)
The dominant role of the US dollar as a global currency allows the Federal Reserve's monetary policy to significantly influence economic and financial dynamics in other countries through mechanisms such as exchange rates, interest rates, and capital flows. This paper examines how shifts in the Federal Reserve's policy can precipitate economic disruptions in peripheral nations, potentially heightening the risk of systemic financial crises. By utilizing the directed acyclic graph (DAG) technique and network topology analysis, we explore the dynamic evolution of systemic risk within global financial markets from a network perspective. Our findings reveal that the US financial market is a net exporter of risk spillovers, whereas China predominantly receives these volatility transmissions. Such systemic financial risks prove contagious across markets. In the wake of Federal Reserve adjustments, China's financial markets invariably experience impacts, compelling them to align with U.S. policy rate changes and thereby compromising China's monetary policy independence.